School Bullying and its Relationship to Academic Achievement among Ninth Grade Students in Al-Khums Schools: An Empirical Study (Comprehensive Journal of Science, 2026)
This research aims to identify the relationship between school bullying and academic achievement among ninth-grade students in schools in Al-Khums city. The research sample consisted of 100 male and female students. The descriptive correlational approach was used, along with two scales: school bullying and academic achievement. Several statistical methods were employed to achieve the research objectives, including Pearson's coefficient, Cronbach's alpha coefficient, t-test, and linear regression. The research concluded that the sample rarely engages in physical, verbal, or social bullying. Statistically significant differences were found between males and females in all types of bullying, favoring females. Furthermore, a statistically significant relationship was found between the combined dimensions of bullying and academic achievement.
Keywords: School bullying, academic achievement, ninth grade